Pengembangan Media Pembelajaran Peluang Berbasis Multimedia Interaktif Untuk Mahasiswa STKIP PGRI PACITAN - Nely Indra Meifiani; Tika Dedy Prastyo (Beta: Jurnal Tadris Matematika, 2015)
This research aims at developing interactive multimedia-based mathematical learning and revealing how the students respond toward the media. The development steps of that interactive mathematical learning media using computer were carried out by development model of ADDIE (Analysis, Design, Development, Implementation, Evaluation). The instrument used to collect the data was media evaluation questionnaires. The data analysis technique was conducted both qualitatively and quantitatively. Based on the research findings that the interactive multimedia-based probability learning revealed no revision and wellreceived by the students. Although there is difficulty for the students at the initial use of it, due to abstract learning habit, but it can be overcome well.